Association of three missense mutations in the homocysteine-related MTHFR and MTRR gene with risk of polycystic ovary syndrome in Southern Chinese women - Wanqin Feng; Yan Zhang; Yuan Pan; Yi Zhang; Minjuan Liu; Yuxin Huang; Yuanling Xiao; Wenyu Mo; Junjie Jiao; Xiaoyang Wang; Dan Tian; Lixia Yang; et al. (BMC, 2021)
Abstract Background The etiology between homocysteine and polycystic ovary syndrome (PCOS) is unclear. In humans, the level of homocysteine is mainly affected by two enzymes: methylene tetrahydrofolate reductase (MTHFR) and methionine synthase reductase (MTRR). While the activity of these two enzymes is mainly affected by three missense mutations, namely C677T (MTHFR), A1298C (MTHFR), and A66G (MTRR). This study aims to examine the association between the three missense mutations and PCOS and investigate whether the three missense mutations exerted their effect on PCOS by affecting the homocysteine level. Methods A case-control study was designed, comprising 150 people with PCOS and 300 controls. Logistic regression analysis was used to assess the association between the three missense mutations and PCOS. Linear regression analysis was used to assess the association between the three missense mutations and the homocysteine level. Mediation analysis was used to investigate whether the three missense mutations exerted their effect on PCOS by affecting the homocysteine level. Results Following adjustments and multiple rounds of testing, MTHFR A1298C was found to be significantly associated with PCOS in a dose-dependent manner (compared to AA, OR = 2.142 for AC & OR = 3.755 for CC; P < 0.001). MTRR A66G was nominally associated with PCOS. Mutations in MTHFR A1298C and MTRR A66G were significantly associated with the homocysteine level. Mediation analysis suggested the effect of MTHFR A1298C on PCOS was mediated by homocysteine. Conclusions MTHFR A1298C and MTRR A66G were associated with PCOS, and MTHFR A1298C might affect the risk of PCOS by influencing the homocysteine level.